Manipulation of choice behavior - Paola Manzini; Marco Mariotti; Christopher J. Tyson (Institute for the Study of Labor (IZA), 2011)
We introduce and study the problem of manipulation of choice behavior. In a class of two-stage models of decision making, with the agent's choices determined by three psychological variables, we imagine that a subset of these variables can be selected by a manipulator. To what extent does this confer control of the agent's behavior? Within the specified framework, which overlaps with two existing models of choice under cognitive constraints, we provide a complete answer to this question.
urn:nbn:de:101:1-201108093211
Keywords: D01; D03; D70; 330; attention; choice function; revealed preference; satisficing; threshold